PERFORMANCE OF FREE WATER SURFACE FLOW CONSTRUCTED WETLAND FOR LEAD AND CADMIUM IONS REMOVAL USING AZOLLA PINNATA PLANT - Huda A. S; S. E. Ebrahim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
Phytoremediation is the ability of some plants to bio accumulate, decompose, or transformation of pollutants in soils, water, or air. In the current study, an effort is made to study the effectiveness of free-floating plants to treat simulated industrial wastewater polluted with Lead and Cadmium ions using Azolla Pinnata plant in a lab condition. Free water surface flow constructed wetland were fed with simulated Cd and Pb ions in different concentrations (5, 10 and 20) mgl-1. Different operating conditions were studied such as; pH, dissolved oxygen, electrical conductivity, temperature, and sodium adsorption ratio to find out the possibility of using treated wastewater for irrigation. Results showed that, Azolla plant had a higher removal efficiency to extract Lead ions (90.1%, 86.67%, and 81.3%) than Cadmium (79.3%, 78.4%, and 69.7%) when the initial concentration is (5, 10, 20) mgl-1 respectively, during 5 days. A slight reducing in pH (8.3 to 7.4) and dissolved oxygen (8.7 to 7.2) mgl-1 observed, all these values mentioned satisfied with the Iraqi standards and World Health Organization. From values of electrical conductivities (250- 750) (µScm-1) and the sodium adsorption ratios (0- 10) it was found that treated wastewater falls into class C2S1 which mean that water has good quality and can be used to irrigate moderately salt-tolerant crops on soils with good permeability.